Development of a Numeracy Literacy Test Instrument with a Bengkulu Cultural Context Based on Android Ispring Suite and AI - Elwan Stiadi; Ari Putra; Diah Selviani (Universitas Bengkulu, 2025)
This study aims to develop a valid and reliable numeracy literacy test instrument with the local cultural context of Bengkulu based on an Android application using iSpring Suite integrated with artificial intelligence (AI). This research was a development research (Research and Development) using the Cennamo and Kalk model which consists of five stages: defining, planning, demonstration, development, and evaluation. The research population was eighth-grade students in junior high schools (SMP) in Bengkulu, totaling 90 students. The research sample was determined using purposive sampling technique of 60 students. The numeracy literacy test instrument was developed based on numeracy literacy indicators from PISA and adapted to the local cultural context of Bengkulu such as tin mining, plantation production, and local wisdom of Bengkulu. Instrument validity was tested through expert judgment and empirical validity using factor analysis, while reliability was measured using Cronbach Alpha. The results showed that the numeracy literacy test instrument developed had achieved a valid category (content validity index = 0.89; construct validity = 0.85) and high reliability (α = 0.928) with 28 valid items from 35 initial items. The Android application based on iSpring Suite with AI integration is able to provide automatic and adaptive feedback to users. This instrument can be used as a contextual and technology-based numeracy literacy assessment and learning tool to improve numeracy abilities of junior high school students in Bengkulu.